The Effectiveness of the Quasi-Class Action Approach: Integration of Problem-Based Learning, Flipped Classrooms, and Generative Learning Models - Tobondo, Yuyun Alfasius; Alfian, Melky; Widnyana , I Gusti Agung Gede; uagadi, Agustanty Ekarini Saptarty; Tarindje, Stella Desrilisa; Melapa, Lidia (Interdisciplinary Journal (IDe), 2024)
This study investigates the effectiveness of integrating Problem-Based Learning (PBL), flipped classrooms, and generative learning to enhance student learning outcomes in Indonesia. Employing the Literature Review method, data were gathered from a range of relevant literature evaluating these three learning models. The findings indicate that the combined approach significantly enhances students' critical thinking skills, motivation, and writing abilities compared to traditional teaching methods. Specifically, the incorporation of PBL encourages students to engage in deep learning through real-world problem-solving scenarios. Meanwhile, flipped classrooms allow for more interactive and personalized learning experiences by enabling students to review instructional content at their own pace outside of class. Generative learning, on the other hand, emphasizes the active creation of knowledge, which further strengthens students' comprehension and retention of material. This research contributes to the development of more effective and adaptive educational strategies in Indonesia, and provides a foundation for further exploration in different educational settings. Moreover, the study highlights the potential for these integrative approaches to address the diverse learning needs of students, ultimately fostering a more inclusive and supportive educational environment.